LIMNOLOGICAL PROFILE AND POLLUTION LEVELS OF DAL LAKE USING CARLSON’S TROPHIC STATE INDEX - MONISA MEHOOB, MASOOD UL HASSAN BALKHI; AND BILAL A. BHAT, ADNAN ABUBAKR, IMTIYAZ QAYOOM (The Bioscan, 2018)
The limnological features and Trophic State Index (CTSI) was used to assess the trophic status of Dal Lake of Kashmir. The air and water temperatures of the lake recorded marked seasonal variation with the overall values of 14.39±1.69 ºC and 13.57±2.38 ºC respectively. Depth (3.14±0.14 m) and transparency (1.93±0.07 m) of the lake were found maximum at site D. TDS and TSS showed an increasing trend from winter to autumn with overall mean values of 159.31±9.20 mgL-1and 102.51±6.45 mgL-1 respectively. pH of the lake was found alkaline throughout the study while as the mean dissolved oxygen concentration was recorded 6.94 ± 0.13 mgL1 . Specific conductivity and free carbon dioxide showed average concentrations of 229.76±11.49 µScm-1 and 2.067±0.46 mgL-1 respectively. Average ammonia concentration recorded in the lake was 201.61±11.62 gL-1 with maximum mean value being observed at site C. Nitrate-nitrogen concentrations were found raised in spring (428.09±28.9µScm-1) and autumn (459.11±22.03 µScm-1) than winter and summer. The total phosphorous concentration of the lake was on the higher side (378.49±20.22 µScm-1) during the study. Both orthophosphate and total phosphorous concentrations showed an increasing trend from colder to warmer months. Carlson’s Trophic State Index was greater than sixty on almost all sites. Thus the study made reflected that the Lake is categorized as eutrophic and needs proper management.